The Potential of Cellulolytic Bacteria to Control Heart Rot Disease (Phytophthora nicotianae) on Pineapple - Reni Savutri Sitanggang; Giyanto Giyanto; Efi Toding Tondok (Jurnal Ilmu Pertanian Indonesia, 2026)
Pineapple (Ananas comosus) is a high-value horticultural commodity whose productivity is frequently reduced by heart rot disease caused by the soil-borne pathogen Phytophthora sp., which can lead to severe infections and yield losses of up to 100%. Cellulolytic bacteria, known for producing hydrolytic enzymes, volatile compounds, and antimicrobial metabolites, are promising biological control agents. This study aimed to isolate and evaluate cellulolytic bacteria from the rhizosphere of Bromeliaceae plants with the potential to inhibit Phytophthora sp. Research activities included rhizobacterial isolation, pathogen identification, cellulolytic screening, biosafety assessment, antagonistic assays (in vitro and semi-in vivo), and molecular characterization of promising isolates. Molecular identification of the pathogen using ITS1/ITS4 primers confirmed its close similarity to the Phytophthora nicotianae strain BG4K3b. Nineteen cellulolytic were obtained, exhibiting diverse cellulolytic indices. Dual culture assays identified A45 (47.11%) and FTA22 (40.99%) as the most effective isolates, whereas volatile compound assays revealed the highest inhibition by FT57 (55.18%) and K5 (44.98%). Semi-in vivo assays on five isolates selected through the Analytic Hierarchy Process demonstrated that all isolates could inhibit lesion development, with FT57 and A45 showing the highest reductions of 73.74% and 71.81%, respectively. Both isolates also produced indole-3-acetic-acid, solubilized phosphate, and exhibited cellulolytic index of 1.83 and 1.18. Molecular identification using 16S rRNA gene amplification (27F/1492R) indicated that FT57 was similar to Bacillus subtilis MS7, whereas A45 was similar to Stenotrophomonas maltophilia Y042. Overall, the isolates FT57 and A45 exhibited strong potential for development as biological control agents to manage heart rot disease in pineapple. Keywords: Bacillus subtilis, biological control agents, Stenotrophomonas maltophilia